Review of Elli Lemonidou, Ιστορία και μνήμη του Α΄ Παγκοσμίου Πολέμου στην Ευρώπη : [History and memory of the First World War in Europe] - Theodosiou, Christina (Historein, 2025)
Review of Elli Lemonidou. Ιστορία και μνήμη του Α΄ Παγκοσμίου Πολέμου στην Ευρώπη [History and memory of the First World War in Europe]. Athens: Papazisis, 2019. 148 pp.